AP-2 complex contributes to hyphal-tip-localization of a chitin synthase in the filamentous fungus Aspergillus nidulans. Issue 10 (October 2021) - Jin, Jingyun; Iwama, Ryo; Takagi, Keiko; Horiuchi, Hiroyuki
Abstract: Filamentous fungi maintain hyphal growth to continually internalize membrane proteins related to cell wall synthesis, transporting them to the hyphal tips. Endocytosis mediates protein internalization via target recognition by the adaptor protein 2 complex (AP-2 complex). The AP-2 complex specifically promotes the internalization of proteins important for hyphal growth, and loss of AP-2 complex function results in abnormal hyphal growth. In this study, deletion mutants of the genes encoding the subunits of the AP-2 complex (α, β2, μ2, or σ2) in the filamentous fungus Aspergillus nidulans resulted in the formation of conidiophores with abnormal morphology, fewer conidia, and activated the cell wall integrity pathway. We also investigated the localization of ChsB, which plays pivotal roles in hyphal growth in A. nidulans, in the Δμ2 strain. Quantitative analysis suggested that the AP-2 complex is involved in ChsB internalization at subapical collar regions. The absence of the AP-2 complex reduced ChsB localization at the hyphal tips. Our findings suggest that the AP-2 complex contributes to cell wall integrity by properly localizing ChsB to the hyphal tips. Highlights: The AP-2 complex recognizes a part of endocytic cargos. Deletion of the AP-2 complex leads to diverse phenotypes in Aspergillus nidulans . The cell wall integrity pathway is activated in the deletion mutants. The AP-2 complex promotes the hyphal-tip-localization of ChsB.